La revista infantil Pelayos: de la Guerra Civil Española a la «nueva época», ¿la existencia de un neocarlismo? - Zoé Stibbe (Cahiers de Civilisation Espagnole Contemporaine)
Eighty-three years after the disappearance of the Carlist children's magazine Pelayos (1936-1938), born just a few months after the outbreak of the Spanish Civil War, it is reborn. Same title, same aesthetic, same ideology: nothing has changed, except Spain. Spain, led by the socialist Pedro Sánchez, was no longer at war. Children's publications are written to be entertaining, a far cry from those that once waged a communication war to enlist and indoctrinate future followers. However, Pelayos magazine –the magazine of the «new era», as stated on the official Traditionalist Communion website at the time of its launch - seems out of time, out of our time. Children are given a discourse frozen in a heritage that, while centuries old and presented to them as an asset, nonetheless remains suspended in a temporal bubble that seems impervious to modern society. And yet, the various movements that make up traditionalism do not hesitate to use the same tools they denounce, for the sake of ideological dissemination.